Strategies for Increasing the Competitiveness of the National Defense Industry in the Digital Age - Haryadi, Airwan; Sulistyadi, Edy; Asmoro, Novky (PT FORMOSA CENDEKIA GLOBAL, 2025)
The defense industry is one of the strategic sectors that has an important role in maintaining the sovereignty and security of a country. In the digital era, the industry faces significant challenges and opportunities, especially in integrating cutting-edge technology to improve its competitiveness. This research analyzes strategies to improve the competitiveness of the national defense industry in the digital era. The method used is a qualitative approach with secondary data from literature, policies and case studies. The results show that digitalization, technological innovation, triple helix collaboration, and technology transfer are the main factors in the development of the defense industry. However, challenges such as cyber threats, limited infrastructure and funding are still an obstacle. This research recommends strengthening government policies, investing in research and development, and developing human resources to support defense equipment independence and global competitiveness.